Quenched Substrates for Live-Cell Labeling of SNAP-Tagged Fusion Proteins with Improved Fluorescent Background - Stöhr, Katharina; Siegberg, Daniel; Ehrhard, Tanja; Lymperopoulos, Konstantinos; Öz, Simin; Schulmeister, Sonja; Pfeifer, Andrea C; Bachmann, Julie; Klingmüller, Ursula; Sourjik, Victor; Herten, Dirk-Peter (Analytical chemistry (Washington), 2010)
Recent developments in fluorescence microscopy raise the demands for bright and photostable fluorescent tags for specific and background free labeling in living cells. Aside from fluorescent proteins and other tagging methods, labeling of SNAP-tagged proteins has become available thereby increasing the pool of potentially applicable fluorescent dyes for specific labeling of proteins. Here, we report on novel conjugates of benzylguanine (BG) which are quenched in their fluorescence and become highly fluorescent upon labeling of the SNAP-tag, the commercial variant of the human O6-alkylguanosyltransferase (hAGT). We identified four conjugates showing a strong increase, i.e., >10-fold, in fluorescence intensity upon labeling of SNAP-tag in vitro. Moreover, we screened a subset of nine BG-dye conjugates in living Escherichia coli and found them all suited for labeling of the SNAP-tag. Here, quenched BG−dye conjugates yield a higher specificity due to reduced contribution from excess conjugate to the fluorescence signal. We further extended the application of these conjugates by labeling a SNAP-tag fusion of the Tar chemoreceptor in live E. coli cells and the eukaryotic transcription factor STAT5b in NIH 3T3 mouse fibroblast cells. Aside from the labeling efficiency and specificity in living cells, we discuss possible mechanisms that might be responsible for the changes in fluorescence emission upon labeling of the SNAP-tag, as well as problems we encountered with nonspecific labeling with certain conjugates in eukaryotic cells.